Participation and womens economic empowerment: clarifying their relationship in community based organization - Ani, Fauziah; Abu Samah, Asnarulkhadi; Damin, Zahrul Akmal; Jaes, Lutfan; Isa, Khairunesa; Md. Yusoff, Rosman; Johar, Siti Sarawati; Hamzah, Johar Shahidah (Science Publishing Corporation, 2018)
Empowerment and participation are viewed as combined strategy in combating poverty particularly in third world countries. It is considered an effective approach in uplifting the status of economy. As a medium, empowerment and participation is believed to play an important role in determining successful economic activity. Based on this premise, this research is conducted to ascertain the relationship between participation level (decision making, implementation and interest acceptance and how far these three levels effect the empowerment of PWPK members in Johor. Around 366 members from 60 Pergerakan Wanita Pekebun Kecil (Movement of Small Woman Farmer groups) have been selected as respondents using cluster multistage sampling. Research data was collected using questionnaires and analyzed using Structural Equation Modelling (SEM) assisted by AMOS 21 software. Research findings shows all three participation levels have average relationship with economic empowerment. On the other hand, participation level in interest acceptance is the most significant predictor when compared to all three levels. Hence, to determine PWPK functions as an empowerment medium, participatory level must be enhanced.